Development and Practice of a School-Based Curriculum for High School Science and Technology Research that Integrates Red Military Industry with Scientific and Technological Innovation Literacy - Yan Feng (Education Research on Study Tours and Practice, 2026)
In the context of reforming educational approaches in regular high schools and integrating the five dimensions of education, science and technology research-based learning has emerged as a vital vehicle for developing school-specific curricula, fulfilling the fundamental mission of fostering moral integrity, and cultivating students 'scientific innovation literacy and patriotic spirit. Leveraging its status as a provincial key high school and capitalizing on the profound red military-industrial heritage and aerospace/oceanic innovation resources of Harbin Institute of Technology and Harbin Engineering University, Harbin No.3 High School has established an integrated "Red Military-Industry + Scientific Innovation Literacy" curriculum through authentic research activities. This study examines the school's organized field trips—including visits to the Harbin Institute of Technology Aerospace Museum, university history museum, and memorial halls at Harbin Engineering University and Harbin Military Industry University—as well as marine culture museums. It systematically analyzes the curriculum's development background, educational philosophy, objective framework, content structure, implementation pathways, evaluation mechanisms, and practical reflections. The research establishes a collaborative, theme-driven, and holistic educational model for research-based learning, providing actionable insights for regular high schools to systematically develop and sustainably implement science and technology research curricula utilizing local military-industrial university resources.